Assessing the Effectiveness of Free Inquiry Learning with a Scientific Approach for Developing Children’s Scientific Skills - Ismail, Ima; Ahmad; Syamsuardi; Herlina (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Buton, 2025)
This study aims to describe the science abilities of group B children before and after the implementation of the free inquiry method at TK Negeri Pembina Bungi. The background of this research lies in the importance of developing science skills from an early age as a foundation for shaping children’s critical, logical, and creative thinking. The free inquiry method was chosen because it allows children to directly explore phenomena in their surroundings, making learning experiences more meaningful and in line with their cognitive development stage. The study employed an experimental approach with a one-group pretest–posttest design. Data were collected through observation, testing, and documentation. The subjects were group B children who actively participated in learning activities using the free inquiry method. Prior to treatment, the children’s science skills were still at an early stage, particularly in understanding basic concepts such as recognizing colors. The findings revealed that there was a notable improvement after the implementation of the free inquiry method. The children not only achieved the expected level of development but some of them also demonstrated very good progress. This indicates that the free inquiry method is effective in enhancing children’s science abilities, as it encourages active involvement, curiosity, and critical thinking skills from an early age. Therefore, free inquiry learning can serve as an alternative instructional strategy to support the achievement of early childhood education goals, particularly in the field of science development.